Politics of Symbolization Across Central and Eastern Europe - Halas, Elzbieta; Halas, Elzbieta; Maslowski, Nicolas (Peter Lang, 2021)
Politics of symbolization affects the semantics of identities and power relations between various subjects, and encompasses the changing meanings of social spaces, times, historical narratives, as well as modalities of collective memory. The volume focuses on politics of symbolization across Central and Eastern Europe understood as complex spaces of semiosis that are rife with similarities and differences. Politics of symbolization consists of various strategies of referring to past collective experiences from the perspective of projected visions and representations of the future. The European Union and its politics of symbolization is relevant in this respect. The volume facilitates understanding of the problems associated with politics of symbolization in Central and Eastern Europe.